Improving engagement between tourists and staff at natural and cultural heritage tourism sites: exploring the concept of interpretive conversations. Issue 1 (2nd January 2018) - Black, Rosemary
ABSTRACT: Natural and cultural heritage tourism organisations offering informal learning environments such as museums, national parks and zoos engage with tourists through a range of techniques including interpretation. This conceptual paper explores the idea of interpretive conversations that is largely unexplored and untapped particularly at nature-based tourism sites. The potential benefits for initiating, encouraging and engaging in interpretive conversations between tourists and staff are discussed. Interpretive conversations have the potential to result in individualised learning experiences, and enhanced connections between tourists, staff and the site, as well as between tourists and the relevant organisations. Examples are drawn from a range of natural and cultural heritage tourism organisations that encourage and support interpretive conversations between tourists and staff and the results of their efforts. Three key strategies to implement interpretive conversations are presented and how they need to be supported by organisational culture and management.